PERSENTASE KEJADIAN Avian Influensa BERDASARKAN DATA SEROLOGIS DI LABORATORIUM SEROLOGI BALAI BESAR VETERINER WATES YOGYAKARTA TAHUN 2011-2013 - , SANDY ARFIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Avian influenza is a dangerous disease in poultry. Avian influenza is very important for detection, as avian influenza can cause high mortality in poultry and can infect humans. Effective measures are needed to determine the individual or population affected by avian influenza. Avian influenza serology can be detected using the test haemaglutination inhibition (HI). HI test was also used to detect bias in antibody titer so that it can be seen that the individual is protected from highly pathogenic avian influenza or not. The purpose of this thesis is to determine the percentage of cases of avian influenza (AI) in the province of Yogyakarta, Central Java and East Java based serological detection using the HI test. Based on the data of serological tests that have been conducted by the Center for Veterinary Serology Laboratory Yogyakarta Wates total of 2011 specimens were positive for antibody serology avian influenza numbered 215, in 2012 amounted to 259, and in 2013 in creasedto 465.